2018
DOI: 10.1093/rheumatology/key059
|View full text |Cite
|
Sign up to set email alerts
|

20 years of experience with tumour necrosis factor inhibitors: what have we learned?

Abstract: TNF inhibitors are biologic DMARDs approved for the treatment of active RA in mid-1990s. They still represent a valuable therapeutic option to control the activity, disability and radiographic progression of the disease. In the context of TNF inhibitors, there are currently several molecules and different administration routes that provide optimal treatment personalization, allowing us to respond to a patient's needs in the best possible way. The increasing use of TNF inhibitors has not only improved the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Currently, several Food and Drug Administration-approved biological inhibitors that broadly inhibit TNF activity across all cell types are in clinical use for the treatment of diverse autoimmune disorders (59). Although of great clinical value, these agents are also complicated by serious adverse events in some patients because of their broad mode of action (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several Food and Drug Administration-approved biological inhibitors that broadly inhibit TNF activity across all cell types are in clinical use for the treatment of diverse autoimmune disorders (59). Although of great clinical value, these agents are also complicated by serious adverse events in some patients because of their broad mode of action (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Mice are the most commonly used models because they are immunologically similar to humans, genetically tractable, and economical. Studies in inbred mice demonstrated the importance of CD4 ϩ T cells, gamma interferon (IFN-␥), and tumor necrosis factor alpha (TNF-␣) among other immunological mediators that are clearly relevant to tuberculosis in humans (5)(6)(7)(8)(9)(10). However, M. tuberculosis infection of the most commonly used inbred mouse strains, such as C57BL/6J (B6) or BALB/c, does not result in all aspects of human tuberculosis or outcomes after vaccination.…”
mentioning
confidence: 99%
“…The single observed improvement for cancer screening was the one related to skin cancer. This probably reflects the current interest in a potential higher risk of skin cancer on tumour necrosis factor inhibitors 36 37…”
Section: Discussionmentioning
confidence: 90%